Minimally Invasive Approach In The Treatment Of Lung Abscess: A Case Report - Rahmat Yusuf Arifin; Rachmad Aji Saksana; Indra Setya Permana; Anggi Fitria Kusumaningtyas (The International Journal of Medical Science and Health Research, 2025)
Background : Lung abscess is characterized by a localized collection of pus or necrotic tissue in the lung parenchyma, which develops into a cavity. Early diagnosis and appropriate management are essential to prevent further complications. Minimally invasive procedures can be performed on lesions larger than 6cm in diameter. Case Report : A 63-year-old man came with a chief complaint of progressive shortness of breath and coughing up blood. The cough had been present for 1 month, accompanied by night sweats, and weight loss. The patient's general condition appeared thin. Physical examination showed decreased fremitus and dull percussion in the left hemithorax. Laboratory results showed leukocytosis with increased neutrophils. Chest radiography showed air-fluid level in the inferior zone and the left parahilar cavity with infiltration suggest a suspected lung abscess. Based on the findings obtained, the patient underwent percutaneous drainage guided by ultrasound ( U S -guided drainage ) using a 14-gauge abbocath needle as a therapeutic procedure. The procedure was performed twice, evacuating 400 cc and 250 cc of purulent fluid. Thoracic radiology evaluation showed resolution of the lung abscess, along with significant clinical improvement in the patient. The patient received metronidazole antibiotic therapy combined with ceftriaxone. The patient underwent treatment for 5 days, before finally being allowed to go home. Discussion: In cases of lung abscess, if conservative therapy using antibiotics does not provide adequate improvement, then invasive intervention such as open surgical procedures is needed. Minimally invasive approaches such as ultrasound-guided percutaneous drainage are an alternative option in areas with limited resources and no computed tomography (CT) facilities. This approach is considered to provide shorter hospitalization and faster recovery. In this case, the percutaneous drainage procedure in cases of lung abscess showed good clinical improvement in the patient. Conclusion: Lung abscess is a serious condition that requires rapid diagnosis and intervention. Ultrasonography-guided percutaneous drainage has been shown to be effective as a therapeutic modality in treating lung abscess . Operator reliability in operating ultrasonography can reduce the risk of complications that may occur.